Prospects of Organic Farming in Bhutan: A SWOT Analysis - Sonam Tashi; Kesang Wangchuk (Advances in Agriculture)
A study was conducted to investigate the prospects of organic agriculture (OA) in Bhutan from the experts’ perspective, particularly the SWOT (strength, weakness, opportunity, and threat) aspect. Thirty-five Bhutanese experts were interviewed. The strengths of OA were (i) good alignment of the principles of OA with Bhutan’s development philosophy, (ii) strong policy and political support, (iii) pristine environment, (iv) OA practices similar to traditional farming, and (v) compatibility of OA with the local farming knowledge. The major weaknesses were (i) a lack of awareness of the benefits of OA, (ii) lack of incentives, (iii) shortage of farm labor, (iv) small and irregular supply of organic product, (v) lack of clarity in policy, (vi) limited plant protection materials, and (vii) a lack of coordination between agencies. Opportunities were (i) a huge regional and global organic market, (ii) promoting healthy lifestyle, (iii) sustainable use of resources, (iv) lowering dependence on food and input imports, (v) development of local organic manure suppliers, (vi) creating seed sovereignty, (vii) conserving local crops, (viii) building soil fertility, (ix) introducing premium price for organic products, and (x) addressing unemployment. Threats included (i) increasing incidences of pests and diseases, (ii) decline in sources of organic manure, and (iii) limited sources of organic manures and fertilizers.